ETHICS AND AESTHETIC VALUE OF SILK IN HADITHS - Azzah Nor Laila; Muhammad Idhom Dzulqarnain (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2018)
Silk is one of the clothing products produced from the time of the Prophet to the present. But in terms of their use, rules and restrictions appear in the hadith of the Prophet. It seems that it has a message that the Prophet wants to convey to his people. This study aims to find the ethical and aesthetic values of silk in the perspective of the Prophet's hadith. Considering the development of fashion fashions made from silk experience development and sometimes its use is debated. The method used in this research is descriptive qualitative. The findings of this study indicate that the ethical values in the traditions surrounding silk can be grouped into three. First, ethics so that Muslims have a firm identity, not relying on other people. Second, ethics so that Muslims avoid arrogance and overdoing in decorating. Third, ethics cares about social affairs and lives simply. The aesthetic value of silk in the hadith can be seen from a variety of terms that refer to clothing made from silk, namely the recitation of ḥarir, dibâj, qasiy, sundus, istabraq, siyara`. The aesthetic value of the variety of clothing made from silk material during the Prophet's time is the uniqueness and variation of the pronunciation used by the Prophet to describe the shapes and structures of various silk types.